Clinical and psychosocial factors associated with domestic violence among men and women in Kandy, Sri Lanka - Piumee Bandara; Andrew Page; Lalith Senarathna; Kumudu Wijewardene; Tharuka Silva; David Gunnell; Duleeka Knipe; Thilini Rajapakse (Public Library of Science (PLoS), 2022)
Domestic violence (DV) is a violation of human rights with adverse intergenerational consequences on physical and mental health. Clinical and psychosocial correlates of DV have been documented internationally, but evidence from South Asia is limited, especially among men. This is a nested cross-sectional study of the control population (N = 856) of a large case-control study in Kandy, Sri Lanka. Multivariable logistic regression models were conducted to estimate the association between clinical and psychosocial factors and experience of DV. Overall associations were examined and stratified by sex and type of abuse. Overall, 19% (95% CI 16%-21%) of the sample reported DV of any form in past year, with a similar prevalence being reported in both men (18% 95% CI 14%-22%) and women (19% 95% CI 15%-23%). Depression symptoms (adjusted OR [AOR] 3.28 95% CI 2.13-5.05), suicidal ideation (AOR 6.19 95% CI 3.67-10.45), prior diagnosis of a mental illness (AOR 3.62 95% CI 1.61-8.14), and previous self-harm (AOR 6.99 95% CI 3.65-13.38) were strongly associated with DV, as were indicators of perceived poor social support (AOR range 2.48-14.18). The presence of in-laws (AOR 2.16 95% CI 1.34-3.48), having three or more children (AOR 2.15 95% CI 1.05-4.41) and being divorced/separated/widowed were also strongly associated with DV (AOR 2.89 95% CI 1.14-7.36). There was no statistical evidence that any associations differed by sex. A multi-sectoral approach is needed to address DV in this context. Enhanced coordination between DV support services and mental health services may be beneficial. Further research and support for men as well as women is needed.